2009
DOI: 10.1098/rsbl.2009.0207
|View full text |Cite
|
Sign up to set email alerts
|

Global changes and animal phenotypic responses: melanin-based plumage redness of scops owls increased with temperature and rainfall during the last century

Abstract: The ecological effects of global climate changes include shifts of species' distribution and changes in migration strategies and phenotype. Colour polymorphism, which can be envisaged as a species' evolutionary response to alternating conditions or to a wide range of habitats, may be affected by climate changes as well. The scops owl (Otus scops) shows two main colour morphs, dark-and pale-reddish, as well as intermediate morphs. We investigated temporal trends in an index of plumage colour of Italian scops ow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 18 publications
3
53
0
2
Order By: Relevance
“…Variation in colour is caused by differential deposition of melanins, mainly pheomelanins, in the feathers (Gasparini et al ). Brown tawny owls have been associated with warm and moist climate and grey owls with dry and cool climate (Galeotti and Cesaris , Emaresi et al , see also Galeotti et al () for similar results in scops owl Otus scops ). In our population the brown colour morph has a lower survival than the grey morph (Brommer et al ) and the difference in survival between the two morphs is strongest in cold and snowy winters (Karell et al ).…”
mentioning
confidence: 83%
“…Variation in colour is caused by differential deposition of melanins, mainly pheomelanins, in the feathers (Gasparini et al ). Brown tawny owls have been associated with warm and moist climate and grey owls with dry and cool climate (Galeotti and Cesaris , Emaresi et al , see also Galeotti et al () for similar results in scops owl Otus scops ). In our population the brown colour morph has a lower survival than the grey morph (Brommer et al ) and the difference in survival between the two morphs is strongest in cold and snowy winters (Karell et al ).…”
mentioning
confidence: 83%
“…(1) Different color patterns may be adaptive under different environmental conditions by providing behavioral or physiological advantages (Galeotti and Cesaris 1996, Galeotti and Rubolini 2004, Galeotti et al 2009). In the Common Guillemot genes for bridling may have a pleiotropic effect, such that color dimorphism may be associated with another property that is the real target of selection.…”
Section: Discussionmentioning
confidence: 99%
“…Galeotti et al (2009) also suggested that the equilibrium between gene frequencies could vary under different conditions and habitats, if the lifetime fitness of different morphs differed between habitats, and that this equilibrium could be disrupted by climate change through direct and indirect effects on fitness. Thus any differences between morphs in their responses to climatic change and any differences in morph frequencies over time may indicate natural selection.…”
Section: Introductionmentioning
confidence: 99%
“…In two species of owl, Eurasian Scops-Owl (Otus scops) and Tawny Owl, the dark reddish morph increased in frequency during the last century in Europe, apparently as a consequence of climate warming (Galeotti et al 2009, Karell et al 2011). These observations suggest that less melanistic individuals survive better in cold FIGURE 1.…”
Section: Climate and Melanin-based Plumage Traitsmentioning
confidence: 99%